Socio Demographic and Clinical Profile of HIV Positive Antenatal Women Registered in PPTCT Centers, Surat, Gujarat - Grishma Chauhan; Anupam Verma; R.K. Bansal; Rachana Prasad (Medsci Publications, 2014)
Objective: The present study reports the socio demographic and clinical profile of 127 HIV positive antenatal women and their husbands. The findings of the study will be helpful for policy decision makers to address the issues of a specific vulnerable group. Materials and Methods: During Jan 2007 to Dec 2008, a total 282 antenatal women were referred to 5 PPTCT centres for HIV testing and counseling. Of these 127 (45%) antenatal women who came to collect their reports could be contacted for this study. The husbands of the 127 HIV positive antenatal women were contacted to collect their information. Result: Mean Age of HIV positive antenatal women was 25.5 ±3.8 years, more than 50% were in the age group of 20-25 years and 18.9% of HIV positive antenatal women were illiterate. HIV positivity rate in spouse was 80%. Two third women were diagnosed HIV positive in 2nd & 3rd trimester of pregnancy. Among the positive 60 (47.3%) were primi gravidas, 27 (21.3%) mothers were not tested for CD4 count. However 98 (77%) mothers were registered in ART centre and 35% HIV positive antenatal women were on ART. Conclusion: HIV positive pregnant women were younger, primi and housewives. HIV positive antenatal women need to be followed rigorously to link them to ART services.